Simulation: An alternative to mass teaching. - Israel Sotolongo Castro; Carlos Pérez Velázquez; Irasema Delgado Ramirez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The simulation is a learning approach method that is must applied systematically in medicine students. We propose two vias of simulation: I. The student or the professor training in the simulation and 2 the tridimentional simulators (Gynecology model), we mention the advantages and disadvantages of this method.